Meningkatkan Keaktifan Siswa Kelas 4 dalam Proses Pembelajaran di MI Yanida - Widia Kartika; Nadia Nurrohmah; Sarah As-Sikah (MANAZHIM, 2020)
In this study, he will examine student learning outcomes using the demonstration method in his learning on Pkn subjects. This study aims to find out how to use the demonstration method, using the demonstration method for learning outcomes of 4th grade students at MI Yanida. Data collection methods in this study use the method namely: Method of observation, interviews. The results of this study will test student learning outcomes taught by using the demonstration method in MI subjects at Yanida MI, the use of demonstration methods by teachers in grade 4 students for Pkn subjects in accordance with the guidelines for implementing good demonstration methods so that good learning results are obtained . from the use of demonstration methods conducted by the teacher. the use of demonstration methods in describing student learning outcomes by using the demonstration method in pkn for grade 4 students shows good results.